Recycling technique and characteristic evaluation of organic/inorganic composite boards. (October 2013) - Lin, Ching-Wen; Lin, Jia-Horng
Nylon 6, one of the major engineering plastic and synthesized fibers, has the following features: good mechanical property, impact resistance, melt flow, and workability. Thus, it is widely used for auto parts, electronic parts, packing films, textiles, etc.; however, plastic waste from processing nylon 6 has also garnered negative attention. This research plans to simulate recycling and reclamation by multiple melt-blending cycles. Only nylon 6, both nylon 6 and carbon fibers, and both nylon 6 and glass fibers are separately melt-blended for 1–10 times with a screw extractor and an injection molding machine, after which the resulting boards—the nylon 6 boards, the nylon 6/carbon fiber boards, and the nylon 6/glass fiber boards—are evaluated for their mechanical properties. According to the experimental results, the nylon 6/carbon fiber boards exhibit an electromagnetic shielding effectiveness above 20 dB; namely it is able to block 90% of electromagnetic waves. Finally, in terms of the mechanical property analysis, the addition of reinforced fibers contributes greater flexibility and impact resistance to the resulting composite boards.